Hontalan esszé - portréfilm Végel Lászlóról . Homeless Essay - Portrait Documentary of Lászlo Végel - Hajdú, Eszter (Hungary, 2009)
Verzio FF Submission A short film portrait of László Végel, a prize-winning Hungarian writer from the multi-ethnic town of Novi Sad (Újvidék), Serbia, just over the border from Hungary. The film follows the writer on a walk in his hometown, the village where he was in hiding, branded as an "enemy” by the Milosevic regime, and talks how his past shaped his ethnic, national, political and social identity.